ON-LINE PLATFORM FOR COMPETENCES DEVELOPMENT IN CORPORATE EDUCATIONAL SYSTEMS - L. G. Andreeva; O. A. Burukina; I. A. Vorob'eva; A. R. Denisov; V. A. Markova; V. P. Novikova; M. M. Stepanova (Russian State Vocational Pedagogical University, 2016)
The aim of the study is to present the model of interaction of university and business corporations in uniform information and educational space, which consists of the uniform requirements to the contents and quality of education and requirements of science; education and business are equally satisfied.Methods. The methods involve summing up the results of the national and international researchers' findings on the problem of vocational pedagogical education; methods of expert survey and system analysis.Results. The information research results disclosing the drawbacks of the existing online-education technologies are presented. There is also a presentation of online-platform concept «The University of the 3rd Millennium» where modern university is considered as a service provider responsible for corporate education. Outsourcing will allow the companies to cut their expenses on employee education programs, while universities will accumulate additional resources by means of developing and selling innovative educational products. The additional funds will enable the university to carry out scientific research, to effectively implement post graduates' employment programs, to introduce innovations.Scientific novelty. The authors define «as is» competences, which the university must have to launch this online-platform project, and «as to be» competences, which every university is to master to successfully implement the project. Internal high-risk systemic tensions and external challenges facing the platform are defined; strategic matrix of their intersection is developed. The latter allowed the authors to specify essential tasks which demand solution within the project. There is also a description of interconnection of the defined tasks with the «as to be» competences, and a Canvas model of the suggested online platform.Practical significance: The authors of the article propose the model of business and education interaction, within which state institutions and local authorities, enterprises and companies with different patterns of ownership will pass corporate education to a modern university, effectively fulfilling the functions of a research, educational and consultative center in many fields.The research results proving readiness of the heads of the companies and organizations (Moscow, St.-Petersburg, Lipetsk, Chelyabinsk, Kostroma) to outsource their corporate education to universities prove that the offered solution is more appropriate than the existing alternatives (systems of additional education in universities, MOOC, corporate universities).